Typification of names in Boraginales described from Sicily - Lorenzo Cecchi; Federico Selvi (Natural History Sciences, 2015)
Eight names in Boraginales (Boraginaceae s.l.) described from Sicily between 1814 and 1919 are typified in the framework of the Flora Critica d’Italia and Loci classici project. Some critical aspects are briefly discussed to clarify the circumstances that led to the choice of the lectotypes and the current taxonomic status of the taxa.